Public Goods and Public Bads - Wolfgang Buchholz; Richard Cornes; Dirk Rübbelke (Center for Economic Studies and ifo Institute (CESifo), 2017)
In many empirically relevant situations agents in different groups are affected by the provision of a public characteristic in divergent ways: While for one group it represents a public good, it is a public bad for another group. Applying Cornes' and Hartley's (2007) Aggregative Game Approach, we analyze a general model, in which such contentious public characteristics are present and are provided cooperatively. In particular, we establish neutrality results w.r.t. redistribution and growth of income, infer the effects of preference changes and coalition building and present a technology paradox. Finally, we compare the outcome of voluntary provision of the contentious public characteristic with the Pareto optimal solution highlighting a potential conflict between equity and efficiency in this case.
Keywords: C72; H41; 330; public goods; public bads; voluntary provision; neutrality